BEHAVIORAL SCIENCE DAN PENDEKATAN BERBASIS DATA DALAM PEMBUATAN KEBIJAKAN BAGI LEMBAGA PEMERINTAH - Gulang, Riska Ana (Jurnal Ilmiah Multimedia dan Komunikasi, 2018)
Measuring the level of achievement of government targets on public policies made and issued in the form of hard policies, must be done with a different approach than the classical style that only uses classical economic models based on value-benefit analysis. This is due to the growing development of internet technology and the speed of data transfer information that is quite high, making it possible to obtain very large amounts of data more efficiently which in the past was difficult to do. Based on research conducted by Stephen Davidovit it was concluded that in the presence of the Internet specifically search engines such as Google, the public / user can behave very honestly, an indication of this can be seen from the keywords used when searching so it is possible to obtain data with a minimum bias for a number of samples. At present there are also new scientific disciplines that are known as the â€œBig Dataâ€ market and the actors are called â€œData Scientistsâ€. These things should be included in consideration when making a policy, so that policies are made right on target. In addition to Big Data currently developing research related to the behavioral aspects / human habits, this research is motivated by Amos Tvesrky and then brought in a more advanced direction by Richard Thaler who won the 2017 Nobel Economics, in the field of behavioral economics. Big data and principles used in behavioral economics are expected to produce policies that are more appropriate and more comfortable to be used by the public.